From the history of translation Kazakh script into Latin graphic in the 1920 and 1930s. - Kassenova, M.D.; Zhumashev, R.M. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The article covers the questions about Kazakh alphabet which was based on Latin graphics in 1920s and 1930s. The authors considered various positions of both supporters of the preservation and reform of Arabic graphic, and supporters of Latinization at the stage of discussion options of the new graphic and implementation of language policy. On basis of the historiographical material and the materials of the first Congress of Kazakh intellectuals in Orenburg in 1924 and the All-Union Turkological Congress in 1926, different views were revealed among the intellectuals on the question about Latinization, viable option of graphics, orthography of Kazakh language and unification of alphabets. The authors arrive at the conclusion that a part of the intellectuals stand against of initiation the new alphabet, explain singularity of Kazakh orthography and originality of the Kazakh language. In Kazakhstan, even before the start of the All-Union Turkological Congress, there was already a positive experience of reforming the Arabic graphics, which was adapted to the sound features of the Kazakh language. Party and state figures, who actively supported the Soviet power, had a different motivation and attitude towards Latinization. The question of reforming Arabic graphics to Latin graphics was illustrated on pages of scientific journals, had a discussion on scientific conferences and congresses, where protagonists and opponents of Latinization argued. The relative freedom of expression characteristic of the first decade of Soviet power was replaced by a rigid command administration that tolerated no dissent. Other opinions were declared hostile and after the repressions of the 1930s, the situation changed, and the issues of language policy were no longer widely discussed.
Keywords: Turkological Congress; national intelligence; Latinization; Arabic graphics; Kazakh language; unification of writing; new alphabet